Analysis of the Preah Vihear Temple Dispute in the Perspective of International Law on the Acquisition of State Territorial Sovereignty - Darminto Hartono; Anisyah Rani (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The Preah Vihear Temple dispute between Thailand and Cambodia is one of the most complex examples of border conflicts in Southeast Asia, which have lasted for more than six decades. The dispute stemmed from differences in interpretation of French colonial maps and claims of sovereignty over the area around the temple. The International Court of Justice (ICJ) in 1962 designated the Preah Vihear Temple as part of Cambodian territory, but tensions continued until finally in 2013, the ICJ reaffirmed Cambodia's sovereignty over the entire temple grounds. This study analyzes the dispute from the perspective of international law on the acquisition of territorial sovereignty, highlighting the principles of estoppel, acquiescence, and uti possidetis juris. It was found that settlement through international adjudication mechanisms provides strong legal legitimacy to Cambodia's claims, while affirming the importance of respect for the boundaries of colonial heritage in accordance with the principles of international law. This dispute also highlights the need to protect the world's cultural heritage in the midst of conflicts between countries.